The Surgically Induced Stress Response. (5th September 2013) - Finnerty, Celeste C.; Mabvuure, Nigel Tapiwa; Ali, Arham; Kozar, Rosemary A.; Herndon, David N.
Abstract : The stress response to surgery, critical illness, trauma, and burns encompasses derangements of metabolic and physiological processes that induce perturbations in the inflammatory, acute phase, hormonal, and genomic responses. Hypermetabolism and hypercatabolism result, leading to muscle wasting, impaired immune function and wound healing, organ failure, and death. The surgery‐induced stress response is largely similar to that triggered by traumatic injuries; the duration of the stress response, however, varies according to the severity of injury (surgical or traumatic). This spectrum of injuries and insults ranges from small lacerations to severe insults such as large poly‐traumatic and burn injuries. Burn injuries provide an extreme model of trauma induced stress responses that can be used to study the long‐term effects of a prolonged stress response. Although the stress response to acute trauma evolved to confer improved chances of survival following injury, in modern surgical practice the stress response can be detrimental.